Dietary Micronutrient Intake of Participants in a "Partners Together in Health" Cardiac Rehabilitation Intervention. Issue 6 (November 2018) - Jensen, Sara Kvien; Yates, Bernice; Lyden, Elizabeth; Krogstrand, Kaye Stanek; Hanson, Corrine
Abstract : Purpose: Current guidelines for cardiovascular health emphasize a "dietary pattern" approach that could be expected to increase intakes of micronutrients in addition to altering the macronutrient profile. However, the effect of interventions such as cardiac rehabilitation on the micronutrient quality of the diet has not been evaluated. Therefore, the goal of this study was to investigate changes in micronutrient intake of cardiac rehabilitation participants over time. Methods: This was a secondary analysis of data from a randomized clinical trial that assessed the effects of the Partners Together in Health intervention on physical activity and healthy eating behaviors. The intake of 9 micronutrients important in cardiovascular health was assessed using 3-d food records. A micronutrient adequacy score was evaluated at 3 time points (baseline, 3 and 6 mo). Changes over time in micronutrient intake were assessed using a general linear model. Results: Sixty-eight participants who were enrolled in the Partners Together in Health interventional trial completed the study. There was no significant difference in the mean micronutrient score at any time point. Intake of individual micronutrients did not improve over the 6-mo time frame with the exception of vitamin E, (8.7 mg vs 6.5 mg for at 6 vs 3 mo, P = .02). The proportion of participants with intakes meeting the Dietary Recommended Intake for each nutrient also remained the same over time. Conclusion: Although cardiac rehabilitation programs may be effective in altering the macronutrient composition, improvements to overall diet quality may be tempered by a lack of improvement in intake of micronutrients. Abstract : Supplemental Digital Content is Available in the Text.Although cardiac rehabilitation has been shown to promote improvements in the macronutrient profile of participants, this study found no improvement in the micronutrient intake during or after a cardiac rehabilitation program.